2012
DOI: 10.3390/ijms13055899
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition of Histamine Release Behavior of Cetirizine Intercalated into Zn/Al- and Mg/Al-Layered Double Hydroxides

Abstract: The intercalation of cetirizine into two types of layered double hydroxides, Zn/Al and Mg/Al, has been investigated by the ion exchange method to form CTZAN and CTMAN nanocomposites, respectively. The basal spacing of the nanocomposites were expanded to 31.9 Å for CTZAN and 31.2 Å for CTMAN, suggesting that cetirizine anion was intercalated into Layered double hydroxides (LDHs) and arranged in a tilted bilayer fashion. A Fourier transform infrared spectroscopy (FTIR) study supported the formation of both the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
(30 reference statements)
1
26
0
Order By: Relevance
“…22 Meanwhile, in another report, Chang liver cells exposed to an LDH nanolayer also exhibited a slight decrease in viability compared with those exposed to its nanocomposite containing cetirizine. 23 Our findings are supported by the above-mentioned studies using nanolayers and their corresponding nanocomposites. The results also indicate that our nanocomposite is likely to be a biocompatible product because it shows less cytotoxicity than pristine The fitting results of the drug release profiles at pH 7.4 and 4.8 based on the three different kinetic models are shown in Figure 7.…”
Section: Surface Propertiessupporting
confidence: 80%
“…22 Meanwhile, in another report, Chang liver cells exposed to an LDH nanolayer also exhibited a slight decrease in viability compared with those exposed to its nanocomposite containing cetirizine. 23 Our findings are supported by the above-mentioned studies using nanolayers and their corresponding nanocomposites. The results also indicate that our nanocomposite is likely to be a biocompatible product because it shows less cytotoxicity than pristine The fitting results of the drug release profiles at pH 7.4 and 4.8 based on the three different kinetic models are shown in Figure 7.…”
Section: Surface Propertiessupporting
confidence: 80%
“…Further evaluation via the formalin test suggested that liposome-encapsulated diclofenac is more effective in suppressing inflammatory pain and that stronger peripheralmediated antinociceptive activity could be attained using the present liposomal formulations. Indeed, encapsulation with liposomes 29 or other materials [30][31][32] will significantly improve a drug's efficacy, and thus reduce its side effects by using lower doses. 33 Similarly to other NSAIDs, the usage of diclofenac is often associated with gastric mucosal erosion, ulceration, hemorrhage, epigastric pain, and platelet dysfunction owing to the inhibition of prostaglandin synthesis by cyclooxygenase enzyme (COX).…”
Section: Discussionmentioning
confidence: 99%
“…14 Owing to the efficient drug-delivery feature of LDH nanocarriers, many pharmaceutically active compounds have been successfully intercalated into the interlayer gallery of LDH. Among them are the cardiovascular drugs fluvastatin and pravastatin; 15 anti-inflammatory drugs such as diclofenac 16 and fenbufen; 17 antihypertensive drugs like perindopril erbumine; 18,19 the antihistamine drug cetirizine hydrochloric acid; 20 and anticancer drugs such as cordycepin, which was intercalated into the gallery of magnesium/ aluminum (Mg/Al)-LDH. It was observed that the resulting nanohybrid had greater stability and a greater suppression effect on U937 cancer cell growth than free cordecypin 3 and methotrexate (MTX).…”
Section: Introductionmentioning
confidence: 99%